2017
DOI: 10.20944/preprints201701.0029.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distal [FeS]-Cluster Coordination in [NiFe]-Hydrogenase Facilitates Intermolecular Electron Transfer

Abstract: Biohydrogen is a versatile energy carrier for the generation of electric energy from renewable sources. Hydrogenases can be used in enzymatic fuel cells to oxidize dihydrogen. The rate of electron transfer (ET) at the anodic side between the [NiFe]-hydrogenase enzyme distal iron-sulfur cluster and the electrode surface can be described by the Marcus equation. All parameters for the Marcus equation are accessible from Density Functional Theory (DFT) calculations. The distal cubane FeS-cluster has a three-cystei… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 36 Recent density functional theory calculations suggest that this is because electrons pass between the outer surface of the protein and the distal cluster via a precise molecular route that terminates at the His ligand ( Supplementary Figure 1 ). 37 , 38 Variants HyaA-K189N and HyaA-Y191E, which mimic differences in this surface-to-histidine route in O 2 -tolerant and O 2 -sensitive [NiFe]-hydrogenases ( Figure 1 ), are generated to investigate the role of residues along this route in tuning E dist .…”
Section: Introductionmentioning
confidence: 99%
“… 36 Recent density functional theory calculations suggest that this is because electrons pass between the outer surface of the protein and the distal cluster via a precise molecular route that terminates at the His ligand ( Supplementary Figure 1 ). 37 , 38 Variants HyaA-K189N and HyaA-Y191E, which mimic differences in this surface-to-histidine route in O 2 -tolerant and O 2 -sensitive [NiFe]-hydrogenases ( Figure 1 ), are generated to investigate the role of residues along this route in tuning E dist .…”
Section: Introductionmentioning
confidence: 99%
“…389 DFT calculations demonstrated that substitution of the histidine ligand to a cysteine in Df [NiFe]hydrogenase does not change the reorganization energy of the distal [4Fe-4S] cluster. 390 The calculated rate of electron transfer was, however, reduced by three orders of magnitude, resulting from a change in electronic donor−acceptor coupling including histidine H184 and phenylalanine F193 (F197 in DvMF). These results indicated that the protein environment is tuned for efficient electron transfer.…”
Section: Medial and Distal Clustersmentioning
confidence: 96%
“…The works of Petrenko and Stein 24 , 25 are rare examples of FO DFT calculations where the wave functions of individual fragments are considered explicitly in the H AB computations. The authors calculate electronic coupling matrix elements for the biological ET process that involves iron–sulfur clusters.…”
Section: Introductionmentioning
confidence: 99%